Comparison of the Concept of Rida in the Qur'an and the Concept of Psychological Well Being - Karimah Darojat; Achmad Khudori Soleh (LECTURES: Journal of Islamic and Education Studies, 2023)
Ridha is the goal of life for muslims. However, several studies have caused ridha to change its meaning to satisfaction, while the meaning of ridha is much more than that. The purpose of this article is to find out the comparison of the concept of ridha in the Qur’an with the concept of psychological well being. The research method used is qualitative with literature study techniques, which is to collecting references and scientific research that is the same as the research purposes. The result of the research obtained are that the concept of ridha in the Qur’an and the concept of psychological well being have similarities when viewed in therms of the aspect they have. With ridha someone will find psychological well being in him too.